2007
DOI: 10.1002/jsfa.2820
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of composition and postharvest performance of organically and conventionally grown kiwifruits

Abstract: Postharvest performance of organic and conventional 'Hayward' kiwifruits grown on the same farm in Marysville, California, and harvested at the same maturity stage were compared in this study. Quality parameters monitored included morphological (shape index) and physical (peel characteristics) attributes of the initial samples. Maturity indices (CO 2 and C 2 H 4 production, firmness, color, soluble solids content and acidity) and content of compounds associated with flavor and nutritional quality (minerals, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
4
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 28 publications
(34 reference statements)
9
53
4
6
Order By: Relevance
“…Estes resultados da relação SST/ATT estão em conformidade com observações de Amodio et al (2007), que determinaram que quivis 'Hayward' produzidos em pomares convencionais apresentam maior SST após 4 meses de armazenamento em relação aos frutos produzidos em pomares orgânicos, mas não houve diferenças entre os sistemas de cultivo quanto à ATT. Já Lester et al (2007) Prange (1992), os frutos produzidos em sistema de cultivo orgânico apresentaram maior teor de SST e não se diferenciaram entre si quanto à ATT.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Estes resultados da relação SST/ATT estão em conformidade com observações de Amodio et al (2007), que determinaram que quivis 'Hayward' produzidos em pomares convencionais apresentam maior SST após 4 meses de armazenamento em relação aos frutos produzidos em pomares orgânicos, mas não houve diferenças entre os sistemas de cultivo quanto à ATT. Já Lester et al (2007) Prange (1992), os frutos produzidos em sistema de cultivo orgânico apresentaram maior teor de SST e não se diferenciaram entre si quanto à ATT.…”
Section: Resultsunclassified
“…Lester et al (2007) verificaram que os pomelos orgânicos apresentaram maior L que os convencionais, em duas das três épocas avaliadas, e menor C em uma das três épocas, sendo os frutos do sistema orgânico mais luminosos e de coloração menos intensa que os frutos de sistema convencional. Amodio et al (2007) verificaram que quivis 'Hayward' de pomar convencional apresentavam-se mais brilhosos e de coloração menos intensa que os quivis de pomar orgânico. Já Roussos e Gasparatos (2009) não observaram diferenças nas variáveis de cor avaliadas em maçãs cultivadas sob sistemas de cultivo orgânico e convencional.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Khoush Ghalb et al (2008) showed that Asian pear at harvesting had large amounts of sucrose that was converted into simple sugars during prolonged storage, which leads to increase of TSS. These metabolic processes coincide with an increase or decrease other compounds, such as acids, soluble pectins, and phenolics (Amodio et al 2007). In current research, TSS values differ among genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…"Hayward" kiwifruits originating from ecological cultivations where only natural fertilisers were used were characterised by thicker peel and smaller flesh surface [Amodio et al 2007] and were firmer than kiwi from the conventional cultivations [Hasey et al 1997]. However, Benge et al [2000] revealed that kiwi from conventional cultivations did not differ in firmness but were characterised by a higher content of soluble stable substances.…”
Section: Streszczeniementioning
confidence: 99%